2020
DOI: 10.1055/a-1146-4236
|View full text |Cite
|
Sign up to set email alerts
|

Adaption of Maximal Glycolysis Rate after Resistance Exercise with Different Volume Load

Abstract: The aim of this study was to investigate the effect of six-weeks of resistance training with different volume load on the maximum glycolysis rate. 24 male strength-trained volunteers were assigned in a high volume low load (50% of their 1RM with 5 sets and reps up to muscle failure) and a low volume high load (70% of their 1RM with 5 sets of ten reps) resistance exercise group. The resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Due to the reduction of enzymes of the energy metabolism in muscle dystrophy, the activity of glycolysis is slowed down [22] . The anaerobic isokinetic strength test in case 1 showed a 6-fold reduced maximum glycolysis rate at the pretest when compared to healthy subjects [28] . The posttest showed a significant increase in the glycolysis rate.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Due to the reduction of enzymes of the energy metabolism in muscle dystrophy, the activity of glycolysis is slowed down [22] . The anaerobic isokinetic strength test in case 1 showed a 6-fold reduced maximum glycolysis rate at the pretest when compared to healthy subjects [28] . The posttest showed a significant increase in the glycolysis rate.…”
Section: Resultsmentioning
confidence: 80%
“…The posttest showed a significant increase in the glycolysis rate. Studies in which multi-week resistance training was performed showed an increase in glycolytic enzymes and the maximum glycolysis rate [15,28] .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, some approaches showed that resistance training was able to increase ν La.max [ 71 ] and that a reduction in training volume may enhance glycolytic capacity and anaerobic performance [ 72 ]. Additionally, hypoxic training methods such as intermittent hypoxic training (IHT) can be effective training strategies to increase anaerobic performance [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced values in our study are in accordance with previous research in ultra-endurance cycling, demonstrating a decrease in during a prolonged period of high-volume low-intensity training ( 65 ). Since was found to be increased by various forms of resistance exercise ( 66 ), an intensified fine-tuning of strength and sport-specific training contents was applied. Our preliminary findings demonstrated that is affected by exercise modality, highest in swimming and lowest in wheelchair racing, which might be due to the usage of muscle mass.…”
Section: Discussionmentioning
confidence: 99%